Contemporaneous oxidation state manipulation to accelerate intermediate desorption for overall water electrolysis. Issue 57 (1st July 2019) - Zhao, Yongqiang; Jin, Bo; Vasileff, Anthony; Jiao, Yan; Qiao, Shi-Zhang
Abstract : Simultaneous oxidation state engineering of Co, N and S for cobalt nitride and sulfide electrocatalysts is demonstrated to facilitate intermediate desorption for OER and HER, leading to efficient overall water electrolysis in a neutral buffer electrolyte. Abstract : Contemporaneous oxidation state engineering of Co, N and S for cobalt nitride and sulfide electrocatalysts is demonstrated to facilitate intermediate desorption for both the oxygen evolution reaction and the hydrogen evolution reaction, leading to efficient overall water electrolysis in a neutral buffer electrolyte.